The petrology and geochemistry of the upper critical zone of the Bushveld complex at the Amandelbult section of Rustenberg Platinum Mines Limited, Northwestern Transvaal, South Africa - Field, Matthew (Rhodes University, Faculty of Science, Department of Geology, 1987)
A study of petrological and geochemical variations through the upper Critical Zone of the Bushveld Complex at Amandelbult section of R.P,M. was undertaken. The sequence at this locality may be divided into seven "units" two of which appear to be complete, possessing the sequence harzburgite-pyroxenite-norite-anorthosite. The other five Units lack basal, intermediate or upper members. Considerable lateral variations are apparent in this sequence, but these are restricted to the Lower Pseudo Reef-Merensky Reef interval, tne same portion of the succession which is affected by pothole structures. The single most important petrographic feature of genetic significance is the occurrence of annealed, recrystallized anorthosite immediately underlying ulstramafic layers. This, together with the undulatory nature of the contact between the two rock layers, suggests that the ultramafic layer was emplaced as a hot liquid over a pre-existing, crystalline anorthosite floor, and that some remelting of this layer occurred. Variations in the chemical make-up of constituent silicate minerals reveal a number of significant processes which may have been operative in the magma chamber prior to crystallization, Olivine grains, for instance, exhibit extremely wide chemical variations both within single layers and from one layer to the next. These variations are best explained by re-equilibration processes with spinel and base metal sulphides, rather than by wide variations in original liquidus compositions. It appears that the compositions of the initial liquids from which each basal olivine-bearing layer crystallized, were approximately similar. Variations in the iron-magnesium ratio of ortho-pyroxenes indicate well defined continuous fractionation trends in units which are considered to be complete. Magnesian compositions are recorded in ultramfic members, while increasingly iron-enriched values are recorded upwards through the sequence pyroxenite-norite-antorthosite. Plagioclase grains exhibit less well defined fractionation trends, but it is clear that an upward increase in An is encountered through indivitual Units. This is in direct contrast to the trend exhibited by orthopyroxene. A further feature of plagioclase grains is the considerable degree of chemical zonation exhibited by them. In cumulus grains this is commonly manifested as strongly reversed rims, while in intercululus grains normal zoning is ubiquitous. Whole-rock chemical variations through the succession indicate that cyclical variations occur through successive Units, but that these merely reflect changes in modal mineralogy and not liquid fractionation trends. Such trends can be shown for selected element ratios, where these elements are known to partition into a single mineral phase. Rations of pyroxene components such as the nickel/scandium ratio, exhibit a saw tooth pattern through successive Units, while ratios of plagioclase components such as the strontium/alumina ratio have unique, fairly constant values for each individual Unit but different values for successive Units. The latter type of cyclicity is not always strictly confined to lithologically recognized boundaries between Units, and a slight overlap into overlying ultramafic layers is apparent. An investigation of variations in trace element levels in a single layer in five widely separated boreholes revealed that there is some evidence for a lateral fractionation trend from the southwest (more primitive) to the northeast (more evolved), although the small number of data points available preclude definite conclusions. There exists in the data some evidence that the Giant Mottled Anorthosite differs chemically from the other anorthosites in the study section, and that it more closely resembles rocks of the Main Zone. This evidence is particularly apparent in variations of the chromium/aluminium ratio of orthoyroxene grains, and in the An content of plagioclase grains, both of whose trends exhibit distinct inflections at the base of this member. The features of the succession at Amandelbult are best explained by the model of Eales et al. (in press, a), which visualizes the input of a number of pulses of new, hot liquid into a magma chamber containing the fractionated residua of previous influxes. At a critical point in time, just prior to the mafic Merensky Reef input, a large input of gabboic liquid was intruded at high levels in the chamber. The lower portions of this liquid mixed with the residua of earlier mafic inputs, which in turn mixed with new inputs of mafic, typical Critical Zone liquids. Thus the lower portions of the study section represent mixtures of new Critical Zone liquids with the residua of previous such influxes, while the upper portions have the added complication of mixture with a Main Zone-type liquid. The unique chemical character of the Giant Mottled Anorthosite appears to be a direct manifestation of the influence of the Main Zone liquid.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Geology -- South Africa -- North-Western Transvaal; Petrology -- South Africa -- North-Western Transvaal